2014
DOI: 10.4103/0259-1162.143109
|View full text |Cite
|
Sign up to set email alerts
|

Liquid ventilation

Abstract: Human have lungs to breathe air and they have no gills to breath liquids like fish. When the surface tension at the air-liquid interface of the lung increases as in acute lung injury, scientists started to think about filling the lung with fluid instead of air to reduce the surface tension and facilitate ventilation. Liquid ventilation (LV) is a technique of mechanical ventilation in which the lungs are insufflated with an oxygenated perfluorochemical liquid rather than an oxygen-containing gas mixture. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They are also the carrier fluid of choice in droplet-based microfluidics. In addition, FC40 carries the vital gases (O 2 and CO 2 ) so effectively that it has been used as a blood substitute ( 17 ), and FC40’s close relatives have been used for liquid ventilation of human preterm neonates ( 18 , 19 ). FC40 also prevents the underlying aqueous layer from evaporating (the solubility of water in FC40 is <7 ppm by weight at room temperature) while isolating each chamber from others in a dish (and from the surroundings), thereby preventing contamination and communication between adjacent chambers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also the carrier fluid of choice in droplet-based microfluidics. In addition, FC40 carries the vital gases (O 2 and CO 2 ) so effectively that it has been used as a blood substitute ( 17 ), and FC40’s close relatives have been used for liquid ventilation of human preterm neonates ( 18 , 19 ). FC40 also prevents the underlying aqueous layer from evaporating (the solubility of water in FC40 is <7 ppm by weight at room temperature) while isolating each chamber from others in a dish (and from the surroundings), thereby preventing contamination and communication between adjacent chambers.…”
Section: Resultsmentioning
confidence: 99%
“…The platform has another significant advantage: It is biocompatible if used with the culture media and dishes (including coated ones; SI Appendix , Fig. S4 A and B ) familiar to biologists, along with what is arguably the most bio-inert immiscible liquid available—FC40 ( 17 19 ). Cells (from bacteria to humans) grow normally in grids ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…PFC also improved the microscopy (see “discussion”). During the microscopy, the animals were subjected to partial-liquid ventilation, a procedure that is not harmful [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, previous studies using Healon to induce RD demonstrated massive histological changes [ 18 – 22 ]. Perfluorocarbon liquids (PFCLs) differ from Healon in that PFCLs can carry oxygen and carbon dioxide [ 23 ]. It is thus possible that some gas-exchange occurs across the subretinal decalin and nourishes the detached retina.…”
Section: Discussionmentioning
confidence: 99%